N‐Terminal Protein Labeling with N‐Hydroxysuccinimide Esters and Microscale Thermophoresis Measurements of Protein‐Protein Interactions Using Labeled Protein. Issue 1 (21st January 2021) - Jiang, Hanjie; Cole, Philip A.
Abstract: Protein labeling strategies have been explored for decades to study protein structure, function, and regulation. Fluorescent labeling of a protein enables the study of protein‐protein interactions through biophysical methods such as microscale thermophoresis (MST). MST measures the directed motion of a fluorescently labeled protein in response to microscopic temperature gradients, and the protein's thermal mobility can be used to determine binding affinity. However, the stoichiometry and site specificity of fluorescent labeling are hard to control, and heterogeneous labeling can generate inaccuracies in binding measurements. Here, we describe an easy‐to‐apply protocol for high‐stoichiometric, site‐specific labeling of a protein at its N‐terminus with N ‐hydroxysuccinimide (NHS) esters as a means to measure protein‐protein interaction affinity by MST. This protocol includes guidelines for NHS ester labeling, fluorescent‐labeled protein purification, and MST measurement using a labeled protein. As an example of the entire workflow, we additionally provide a protocol for labeling a ubiquitin E3 enzyme and testing ubiquitin E2‐E3 enzyme binding affinity. These methods are highly adaptable and can be extended for protein interaction studies in various biological and biochemical circumstances. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Labeling a protein of interest at its N‐terminus with NHS esters through stepwise reaction Alternate Protocol : Labeling a protein of interest at its N‐terminus with NHS esters through a one‐pot reaction Basic Protocol 2 : Purifying the N‐terminal fluorescent‐labeled protein and determining its concentration and labeling efficiency Basic Protocol 3 : Using MST to determine the binding affinity of an N‐terminal fluorescent‐labeled protein to a binding partner. Basic Protocol 4 : NHS ester labeling of ubiquitin E3 ligase WWP2 and measurement of the binding affinity between WWP2 and an E2 conjugating enzyme by the MST binding assay